2020
DOI: 10.1111/ppa.13220
|View full text |Cite
|
Sign up to set email alerts
|

Ralstonia solanacearum preferential colonization in the shoot apical meristem explains its pathogenicity pattern in tomato seedlings

Abstract: Ralstonia solanacearum causes a lethal bacterial wilt disease in many plants by colonizing the vascular tissues of the hosts. Upon inoculation of tomato seedlings through either leaf or root, the wilting symptoms occur first at the apical region and then proceed downward along the shoot. The systemic order of the disease initiation and progression in the host, independent of the site of pathogen inoculation, is yet to be investigated. To understand the disease progression more clearly, we have carried out a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Due to small size, the entire seedling could be stained at regular intervals after the infection. By gus staining, it is observed that R. solanacearum colonizes the shoot apical region of the seedlings within 24h of inoculation either in root or in the leaf [15]. This provides explanation for two important observations i.e.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Due to small size, the entire seedling could be stained at regular intervals after the infection. By gus staining, it is observed that R. solanacearum colonizes the shoot apical region of the seedlings within 24h of inoculation either in root or in the leaf [15]. This provides explanation for two important observations i.e.…”
Section: Discussionmentioning
confidence: 82%
“…(i) The initiation of the disease from the apical region, (ii) Why the disease magnitude is higher by leaf inoculation than by root inoculation [15]. This finding has given a new insight to the disease mechanism.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…R. solanacearum is responsible for >30% losses in yield of C. longa (turmeric), C. aromatica (wild turmeric), and C. zedoaria (white turmeric) in Okinawa, Japan (Ajitomi et al 2015). Meristem tips (without vascular tissues) of plants infected with R. solanacearum have been identified as disease-free zone of the tissue (Kabyyashree et al 2020). Apical meristem cutting and meristem culture play an important role in eliminating the bacterial, fungal, or even viral particles from the host plants (Ramgareeb et al 2010).…”
Section: Introductionmentioning
confidence: 99%